Yield, quality and nutrient accumulation in watermelon as a function of organo-mineral fertilization - Oliveira Filho, Francisco Sales; Pereira, Francisco Hevilásio Freire; Brito, Marcos Eric Barbosa; Medeiros, Joyce Emanuele; Lacerda, Francisco Hélio Dantas; Campos Júnior, José Eustáquio (Comunicata Scientiae, 2019)
The study aimed to assess the yield, nutrients accumulation and fruit quality of watermelon grown under different NPK rates provided by mineral and organic fertilizers. The experiment was performed at the Federal University of Campina Grande (UFCG), Campus Pombal-PB, during the period from June to September 2013. Treatments consisted of three nutrient concentrations N, P and K (50, 100 and 150% of NPK recommendation for watermelon) and five ratios of mineral and organic fertilizer (100/0, 75/25, 50/50, 25 / 75 to 0/100). The experimental design was in randomized blocks, in a 3x5 factorial scheme with four replicates. The NPK rate corresponding to 100% was 120 kg ha-1 respectively for N, P and K. The following variables were evaluated: fruit yield, nutrient accumulation, titratable acidity, soluble solids and ratio between soluble solids and titratable acidity. The concentration of 150% of nutrients was more effective in increasing the yield for the 75/25, 25/75 and 0/100 ratios of mineral and organic fertilizers, and the concentrations of 100 and 150% were the most effective in the accumulation of soluble solids when applied in the mineral and organic fertilizer ratios of 75/25 and 50/50.